An Economic Analysis of Factors Influencing the Adoption of the First Nations Land Management Act and the Consequences of Adoption - Chen, Ying (University of Guelph, 2015)
This thesis provides an overview of the key institutional changes associated with the FNLMA, by highlighting the main differences between the Indian Act and land codes. This thesis then identifies two research questions that require further empirical assessment. First, this thesis investigates which factors influence whether a First Nation will adopt the FNLMA using The probit and ordered-probit models. The findings suggest that the distance to an urban center and the proportion of First Nation Band population living on reserve are important factors. Second, two statistical techniques (difference-in-differences method and propensity score matching method) were used to assess the effect of the FNLMA on better economic outcomes. The results show no significant evidence of economic gains associated with the FNLMA participation. This finding may be the result of the low numbers of First Nations who have implemented the land codes and the limited time for land codes to have effect.